2001
DOI: 10.1258/0022215011909099
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumour of the parotid gland

Abstract: Solitary fibrous tumours are rare tumours originally described in the pleura. More recently there have been reports of these tumours arising at other sites including the parotid region. They are characterized histologically by a variety of growth patterns that can be confused by the unwary with other benign or malignant tumours particularly sarcomas. We present a case occurring in the pre-auricular region which presented diagnostic difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
0
18
0
1
Order By: Relevance
“…For some time, it was incorrectly supposed that the tumor was of mesothelial origin giving rise to names such as localized fibrous mesothelioma, localized mesothelioma, and solitary fibrous mesothelioma [25]. However, it was later demonstrated that this neoplasm was of mesenchymal origin, probably from adult mesenchymal stem cells, developing in almost any anatomic site [12,26,27]. For these reasons, SFT is now the preferred term [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For some time, it was incorrectly supposed that the tumor was of mesothelial origin giving rise to names such as localized fibrous mesothelioma, localized mesothelioma, and solitary fibrous mesothelioma [25]. However, it was later demonstrated that this neoplasm was of mesenchymal origin, probably from adult mesenchymal stem cells, developing in almost any anatomic site [12,26,27]. For these reasons, SFT is now the preferred term [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, he had a 10 years history of a parotid gland mass, so it seems unlikely that trauma is a true etiologic factor. While the histogenesis is still unproven, immunohistochemical and ultrastructural examination have shown that SFT is most likely derived from adult mesenchymal stem cells [12,26]. Throughout the body, as well as in the head and neck region, SFT affects males and females with the same frequency [1,8,16,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations